mplementasi Algoritma HECTOR SLAM Dalam Melakukan Pemetaan Indoor Menggunakan Robot Automated Guided Vehicle - Izzatullah, Muhamad Khosyi (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
Developments in the industrial world are increasingly rapid along with technological developments,autonomous robots are one of the many developed and used in the industrial world and become importantwhich is widely used in various industrial sectors. Autonomous robots move using navigation systems torecognize the environment, navigation has an important role in autonomous robots but navigation requires anaccurate map with the surrounding environment so that the robot can move in accordance with theenvironment. In this study, mapping accuracy analysis was carried out using the Hector-SLAM algorithmmethod to map the surrounding environment by simulation and real-time (robot). This research has severalimportant compounds including robot operating systems (Robot Operating System), data filters such as hectorscan matching where to construct the data obtained, the type of sensor is very influential on the quality of themap produced. This study tests whether the hector scan matching algorithm can do environment mappingaccurately. The results of this study can be concluded that, the map produced from the simulation and robot(real) has a fairly good accuracy, this is based on matching the results of the simulation mapping and robot(real) which has an accuracy of SSIM: 77.26%, MSE Error: 3.96%, Pixel Match: 55.46% of the robot mappingresults (real) while from the simulation results are displayed in the 2nd scenario used to compare with robotsobtained accuracy of SSIM: 87.29%, MSE Error: 1.65% and Pixel Match: 81.11%.